Imaging Recommendations for Diagnosis, Staging and Management of Treatment-Related Complications in Cancer - Mukhopadhyay, Sumit; Sen, Saugata; Ghosh, Priya; Gehani, Anisha; Patra, Anurima; Chandra, Aditi; Chatterjee, Argha; Lingegowda, Dayananda; Gupta, Bharat; Gupta, Meenu; Venugopal, Prakash; Chakraborty, Amrita; Pathak, Ketul K.; Mishra, Pradipta Kumar; Khoda, Jeevitesh (Indian Journal of Medical and Paediatric Oncology, 2023)
Precision medicine is becoming increasingly common in oncology, with treatments tailored to individual patients and cancer. By integrating these underlying concepts of health care, chemotherapy and radiotherapy can be tailored to improve safety and efficacy. On the other hand, oncology treatment regimens may result in local and systemic changes and complications depending on the type of treatment. For the proper and prompt management of cancer patients, it is essential to interpret this posttreatment imaging correctly. This article aims at guiding treating physicians to be able to distinguish complications from expected posttreatment changes.
Keywords: complications; oncology; radiology; review